Estudio ergonómico de los puestos de trabajo en la bodega Ambato Samanga de la corporación eléctrica del ecuador unidad de negocios Transelectric Celec-Ep, programa para prevención de trastornos músculos esqueléticos. - Ramón Fonseca, Edgar Roberto (2018)
The ergonomic study of the positions and activities of critical work is done to improve working conditions, welfare worker health, productivity demands, quality of services at the Bodega de Ambato Samanga, the Electricity Corporation of Ecuador CELEC EP-TRANSELECTRIC Business Unit, an organization that took the important decision to carry out a study of lighting and ergonomic evaluation of jobs in the cellar. To this end, it was necessary to analyze the levels of labor, ergonomic risks qualitatively and quantitatively through surveys with methods such as Reba and OCRA. To detect musculoskeletal discomfort reported by workers, surveys were applied to study personnel, where it was observed that 92% of respondents if they refer symptoms musculoskeletal, based on this existing ergonomic hazards were determined and proceeded to perform the evaluation using recognized international methods, it is so Reba methodology for evaluating stress positions, OCRA was used to assess exposition to repetitive movements of the upper limbs, during their working lives. After the evaluation results are applicable to all workers in the study areas because they all perform the same activity, all data of the valuations were high ergonomic risk and suggest that you should make immediate changes to prevent disease were obtained professionals over time.